2022
DOI: 10.26434/chemrxiv-2022-285bs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anaerobic Hydroxylation of C(sp3)–H Bonds Enabled by the Synergistic Nature of Photoexcited Nitroarenes

Abstract: A photoexcited nitroarene-mediated, anaerobic C–H hydroxylation of aliphatic systems is reported. The success of this reaction is due to the bifunctional nature of the photoexcited nitroarenes, which serve as the C–H bond activator and the oxygen atom source. Compared to previous methods, this approach is cost and atom economical due to the commercial availability of the nitroarene, the sole mediator of the reaction. Owing to the anaerobic conditions of the transformation, a noteworthy expansion in substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Parasram and co-workers demonstrated that photoexcited nitro-compounds can act as hydrogen-atom abstracting agents and promote the anaerobic oxygenation of C(sp 3 )–H bonds. Estrone acetate and ibuprofen methyl ester were among the complex substrates that successfully delivered their corresponding benzyl alcohol . Itami and co-workers found acridinium species able to reduce (diacetoxyiodo)­benzene (PIDA).…”
Section: Late-stage Aliphatic C(sp3)–h Bond Functionalizationmentioning
confidence: 99%
“…Parasram and co-workers demonstrated that photoexcited nitro-compounds can act as hydrogen-atom abstracting agents and promote the anaerobic oxygenation of C(sp 3 )–H bonds. Estrone acetate and ibuprofen methyl ester were among the complex substrates that successfully delivered their corresponding benzyl alcohol . Itami and co-workers found acridinium species able to reduce (diacetoxyiodo)­benzene (PIDA).…”
Section: Late-stage Aliphatic C(sp3)–h Bond Functionalizationmentioning
confidence: 99%